Osteoporosis and Risk Factors among Postmenopausal Women in Integrated Health Post for Elderly - Diana Lyrawati (Journal of Global Pharma Technology, 2019)
Abstract Objectives: The availability of prevalence data for osteoporosis in Indonesia is limited due to the constrained access to BMD measurements, especially in rural areas. Integrated Health Post for the Elderly (Posyandu Lansia) is one of the Indonesian government's programs to monitor and provide health care for the elderly, including postmenopausal women. This study aimed to determine the prevalence of osteoporosis and related risk factors in postmenopausal women. Methods: Respondents were 249 postmenopausal women from 440 people who attended the Posyandu Lansia from 9 villages in Sidoarjo. Quantitative ultrasound was used for calcaneal BMD measurement; other data were collected via questionnaires and enumerated by trained villagers. Results: Our study revealed that the prevalence of osteoporosis postmenopausal women was 73.5%. The osteoporosis risk factors of age, BMI, weight, and menopause duration were associated with T-scores both individually (p<0.05) or simultaneously (p< 0.001), while menopause age and exercise did not. Conclusions: Groups possessing high-risk factors associated with a high prevalence of osteoporosis are postmenopausal women age ≥ 65 years, BMI < 20 kg/m2, weight < 58 kg and duration of menopause > 6 years. Regardless of the groupings, the prevalence of osteoporosis was very high in postmenopausal women. Dietary and exercise adjustments as well as pharmacotherapy may be required to improve their bone health.